2020
DOI: 10.1186/s12861-020-00218-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of the scaffold protein Discs large 5 in the control of growth, cell polarity and cell adhesion in Drosophila melanogaster

Abstract: Background Scaffold proteins support a variety of key processes during animal development. Mutant mouse for the MAGUK protein Discs large 5 (Dlg5) presents a general growth impairment and moderate morphogenetic defects. Results Here, we generated null mutants for Drosophila Dlg5 and show that it owns similar functions in growth and epithelial architecture. Dlg5 is required for growth at a cell autonomous level in several tissues and at the organism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Our data shows that TXT-1 and CEH-58 genetically interact as part of an intracellular signaling cue in the C. elegans body wall muscle, corroborating a previous yeast-two-hybrid study that demonstrated direct interaction between both proteins [38]. Although our study is the first to note an association of TXT-1 with the heat stress response in C. elegans, its closest human orthologue, DLG5, is a membrane associated guanylate cyclase that is part of the Hippo pathway [59,60] and is involved in the cellular response to heat stress [61].…”
Section: Discussionsupporting
confidence: 90%
“…Our data shows that TXT-1 and CEH-58 genetically interact as part of an intracellular signaling cue in the C. elegans body wall muscle, corroborating a previous yeast-two-hybrid study that demonstrated direct interaction between both proteins [38]. Although our study is the first to note an association of TXT-1 with the heat stress response in C. elegans, its closest human orthologue, DLG5, is a membrane associated guanylate cyclase that is part of the Hippo pathway [59,60] and is involved in the cellular response to heat stress [61].…”
Section: Discussionsupporting
confidence: 90%
“…Highly conserved between vertebrates and invertebrates, DLG5 is a scaffold protein with multiple functions, including cell growth, polarity, and adhesion. Knockdown of DLG5 in Drosophila melanogaster has been shown to cause a reduction in wing growth targeting cell proliferation [ 56 ]. In the testis histology images ( Figure 5 ), it can be seen that there are many spermatogonia in the Cq-IAG -silenced group, but they do not appear to be progressing to mature spermatozoa as seen in the healthy control testis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have reported that PFKFB3-kinase activity attenuates the activation of T cells, and demonstrated the effectiveness of PFKFB3 antagonists, even in small amounts, as T cell immunosuppressive agents (55). One of the differentially expressed genes, KLF9, has been previously identified as differentially expressed in T cells from patients with autoimmune rheumatoid arthritis (56), while another, DLG5, is involved in the HIPPO pathway and modulated TGFB signaling (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%